THE CASE REPORT OF A COVID-19 PATIENT WITH LATE DIAGNOSIS OF HIV - Desdiani, Desdiani (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
Coronavirus 2019 (Covid-19) is a disease that causes hyper-systemic inflammation affecting the respiratory system and extrapulmonary system. Covid-19 causes non-specific clinical health disorders in immunocompromised patients who often do not react to treatment. One case of a 58-year-old Indonesian man with a positive GeneXpert test result for Covid-19 but did not react to routine Covid-19 first-line therapy. The patient's anti-HIV test was confirmed positive, with an absolute CD4 of 13.7 cells/L, lactate dehydrogenase of 385 U/L, and procalcitonin of 0.24 ng/mL. The patient was treated with antibiotics, remdesivir, dexamethasone, heparin, anti-HIV treatment, and other supporting medications. The PCR test was negative ten days later, the laboratory and radiology results had also stabilized. In this case, the possibility of co-detection of Covid-19 with immune system diseases such as HIV is emphasized, and the importance of further testing for suspected patients to provide accurate treatment. It is quite difficult to determine HIV risk factors, and the limited treatment options for Covid-19 and it may not be effective. This case highlighted the possibility of misdiagnosis, especially during an infectious disease pandemic, and the importance of extended testing, even if the immunological state is disregarded in immune-compromised patients.